Atividade docente e subjetividade: sentidos e significados constituídos pelo professor acerca da participação dos alunos em atividades de sala de aula - Soares, Júlio Ribeiro (2011)
The main objective of our thesis is learning the teacher s constitution of senses about his/her way of mediating and be mediated by the students participation in classroom activities. In order to achieve it, in addition to Aguiar s and Ozella s (2006) core meaning proposals -- which provided us with a significant contribution in the data abstraction process, enabling us to reach its historical and dialectical materiality -- another important contribution stemmed from Clot s (2006) simple and crossed autoconfrontation s methodological proposal. This particular proposal, as well as the core meaning proposal, is theoretically based on Vigtoski and collaborators socio-economic assumptions. When using those proposals, we started by supposing that, while learning from the teacher in movement, we might be creating on him/her new zones of sensing. Although the teacher in principle follows a planning-based activity, it is the reality on which he/she acts that determines the achieved reality functionality. Therefore, the achieved activity is more complex than it looks like. Both, subjective and objective elements, contradictorily determine the teacher s actual activity. Even if that is not clearly perceived by him/her, the thermometer of his/her actions is, therefore, measuring the objective and subjective reality that constitutes the classroom, and not in the planning s objective inflexibility. So, in addition to the work s objective conditions, it is necessary bear in mind that the teacher s participation quality in the teaching and learning process is mediated also by the way it reflects the students participation in the process, and vice-versa. We, therefore, intend to underscore that, in addition to teaching and learning objective conditions, we ought to consider that the person s psychological state is part of the process. From the auto-confrontations performed with the teacher, we could abstract many of the mediations that have been part of his/her motivations, thus getting near his/her senses regarding the free professor activity. At the same time, we cannot but emphasize that the auto-confrontations also enabled him/her to at least potentiate if not fully achieve the constitution of new senses, thus opening a remeaning process (although a slow one) of his/her way to mediate and be mediated by the students participation in classroom activities